Planetary exploration in the time of astrobiology: Protecting against biological contamination - Rummel, John D. (The National Academy of Sciences, 2001)
These are intriguing times in the exploration of other solar-system bodies. Continuing discoveries about life on Earth and the return of data suggesting the presence of liquid water environments on or under the surfaces of other planets and moons have combined to suggest the significant possibility that extraterrestrial life may exist in this solar system. Similarly, not since the Viking missions of the mid-1970s has there been as great an appreciation for the potential for Earth life to contaminate other worlds. Current plans for the exploration of the solar system include constraints intended to prevent biological contamination from being spread by solar-system exploration missions.